MappingThe Landscape of Game-Based Cultural Diplomacy: A Bibliometeric Analysis of Global Trends and Influential Research - Azis, Muhammad Abdul; Angelina, Nadia (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Video games are becoming an important part of cultural diplomacy. They let countries show off their national identity and soft power around the world. In the past, Japan and Poland have utilized video games to spread their cultural values and get along better with other countries. For instance, Japan's "Cool Japan" campaign and Poland's smart gift of The Witcher series. With the debut of Black Myth: Wukong, an action RPG that combines Chinese mythology with modern gameplay, China has joined the trend. This study looks at nine scholarly papers from 2015 to 2024 that are listed in Scopus and Web of Science. It focuses on how video games are used in cultural diplomacy. The study examines the evolution of game-based cultural diplomacy globally through the analysis of research trends, significant figures, and notable works. The research examines the utilization of video games for diplomacy, nation branding, and cultural interaction, using Japan, Poland, and China as case studies. The results demonstrate that more and more people think that video games are a powerful and changing tool to influence people's thoughts, get people talking to each other around the world, and affect politics around the world. This study gives us vital information about how gaming, diplomacy, and soft power are becoming more and more intertwined. It also lets researchers and politicians see how video games can change international relations in the future.